Quite literally : Volume 1 -5 - Diözesanmuseum, Köln; Kraus, Stefan; Plotzek, Joachim; Surmann, Ulrike; Winnekes, Katharina (Köln : Diözesanmuseum, 1996)
About the Idea and the Task of the Diözesanmuseum in Cologne ; A Natural Place for Art. About the Relationship Between Art and Museum Architecture ; About the history of the Diözesanmuseum in Cologne ; Museum of Reflection or the Squaring of the Circle ; Art for All - but Even More For The Individual
Engels
boek